ASSOCIATION BETWEEN PATHOLOGICAL PERSONALITY TRAITS AND DEFENSE MECHANISMS IN HEALTHY SAMPLE: A PILOT STUDY RESULTS - Ivzāns, Igors; Mihailova, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This article aims to define what kind of relationship exists between pathological traits and defense mechanisms. Primary data, collected from 14th until 30th of March in 2017, was used in this research. Thirty participants (57 % males) in the age of early adultness (from 25 to 39 years, M = 29.9, SD = 3.33) filled in two questionnaires: The Multidimensional Clinical Personality Inventory (Perepjolkina, Koļesņikova, Mārtinsone, & Stepens, 2017) and Defense mechanisms questionnaire (Subbotina, 2017). Six of eight analyzed defense mechanisms (repression, regression, rationalization, displacement, denial and psychological projection) showed statistically significant correlation with at least one pathological personality trait both on facet and on domain level. Some weak (p > .05) correlations were found between some personality traits and two left defense mechanisms: reaction formation and sublimation. Most of correlations were with neurotic defenses according to Vaillant (1992) classification, in particular with repression and displacement. All together 26 traits correlated with neurotic defenses. With other defenses, just a few traits correlated – three traits with mature defenses, two traits with immature defenses and two with psychotic defenses. Received results need to be validated in the future studies and may be useful for clinical psychologists for better understanding of their clients.